Информационно-географическое обеспечение программы по созданию «Единого республиканского цифрового территориального кадастра Крыма» - Карпенко, С.А. (Культура народов Причерноморья, 2003)
Primary results of the Program on creation of “Unified Republican Digital Territorial cadastre of Crimea” were observed and analyzed. Structural functional model of the land management system and the concept of “Geographical ensuring of territorial management” introduced by the author served as a theoretical basis for the research. Major componentry of geographical ensuring were discovered. There are: models if management objects, regional databanks, technique of inventory of activity of subjects of management.